Evaluasi Pemahaman dan Praktik Ajaran Sehat Menurut 2 Timotius 1:1-18: Studi Kasus pada Pelayan di Jemaat GPdI “El Shadday” Sukowono Jember - Jek Ming; Daud Manno (KHARISMATA: Jurnal Teologi Pantekosta, 2023)
This research shows that the values in II Timothy 1:1-18 can build practical theology that is relevant to the problems in GPdI Sukowono. This study produces several instruments that can be used to evaluate congregational problems in general regarding efforts to maintain healthy teachings in the congregation. Maintaining Healthy Teachings is a legacy of faith that requires consistency, sincerity, and faith. Thus the description of the values described can be developed into an instrument in assessing how believers should continue to pay attention to their daily spiritual life.